Precision Among Internet Search Engines: An Earth Sciences Case Study - Lisa A. Wishard (Issues in Science and Technology Librarianship)
Three representative queries related to the earth sciences were used to evaluate the precision of 37 Internet search engines. The structure of three main types of Internet search engines and strategies for improving search results are discussed. The sample queries indicated that Go2, InfoMine, and Argus Clearinghouse had the highest precision for catalog type search engines. Excite, Infoseek and Northern Light had the highest precision for keyword type search engines. There was no one best multiple-threaded search engine. Searchers are urged to use multiple tools when using Internet search engines to locate subject specific queries.